Clinical evaluation of physician-controlled guidewire manipulation during endoscopic ultrasound-guided hepaticogastrostomy (with video) - Nishiguchi, Kyohei; Ogura, Takeshi; Nishioka, Nobu; Ueno, Saori; Okuda, Atsushi; Yamada, Tadahiro; Yamada, Masanori; Ueshima, Kazuya; Higuchi, Kazuhide (Endoscopy International Open, 2021)
Background and study aims Endoscopic ultrasound (EUS)-guided hepaticogastrostomy (HGS) may be most complex because of the EUS-guided biliary drainage procedure and variations in the course of the intrahepatic bile duct compared with the common bile duct (CBD). Appropriate guidewire insertion is essential. Physician-controlled guidewire manipulation (PCGW) might improve technical success rates of bile duct cannulation. The present study aimed to determine the technical feasibility and safety of PCGW during EUS-HGS.Patients and methods A total of 122 consecutive patients who were scheduled to undergo EUS-HGS between October 2017 and April 2019 were prospectively registered. The primary endpoint was the technical success rate of guidewire insertion into the CBD or hepatic hilum. Guidewire insertion was considered to have failed if the HGS assistant failed to achieve manipulation. Results The intrahepatic bile duct was successfully punctured in 120 of 122 patients. During guidewire insertion by the HGS assistant, guidewire fracture was observed in one patient. The guidewire was successfully inserted into the biliary tract and manipulated by the HGS assistant in 96 patients. PCGW was thus attempted for the remaining 23 patients. The guidewire was inserted by PCGW in all 23 patients, improving the technical success rate for guidewire insertion from 80 % to 100 %. After tract dilation, we deployed covered metal stents and plastic stents in 117 and two patients, respectively. The overall technical success rate for EUS-HGS was 97.5 % (119/122). Adverse events comprising bile peritonitis or leakage developed in five patients.Conclusion PCGW might contribute to improving the success rate of EUS-HGS.